Evaluation of carotid intima-media thickness and flow-mediated dilatation in middle-aged patients with nonalcoholic fatty liver disease - Ghasemi-Rad M; Mohammadi; Habibpour (Vascular Health and Risk Management, 2011)
Afshin Mohammadi1, Homayoon Habibpur Sedani2, Mohammad Ghasemi-Rad31Department of Radiology, 2Student Research Committee, 3Genius and Talented Student Organization, Student Research Committee, Urmia University of Medical Sciences, Urmia, West-Azerbaijan, IranBackground: Nonalcoholic fatty liver disease (NAFLD) has a high prevalence in the general population and is the most common liver disease in Western countries. It is a feature of metabolic syndrome and is characterized by excessive accumulation of fat in the liver cells.Methods: We examined 84 consecutive middle-aged (under 45 years) patients with NAFLD and 65 control subjects matched for age, gender, and body mass index to determine carotid intima-media thickness (CIMT) and flow-mediated dilatation (FMD) in the brachial artery.Results: There was a statistically significant difference between CIMT and percentage increase in FMD in the patient group (P = 0.002; r = 0.33) when compared with the control group (P = 0.97; r = 0.005). The mean ± standard deviation CMIT was 0.65 ± 0.09 mm in patients and 0.55 ± 0.07 mm in controls. This difference was statistically significant (P = 0.001). Mean FMD in patients was 6.4% and 15.7% in controls. This difference was statistically significant (P = 0.001).Conclusion: This study shows that pure NAFLD without metabolic syndrome in middle-aged subjects is strongly associated with morphological (CIMT) and physiological (FMD) changes. These findings may have an important role in increasing cardiovascular risk in these patients.Keywords: nonalcoholic fatty liver disease, carotid intima-media thickness, flow-mediated dilatation